Kromium serum dan asupan mikromineral pada penyandang diabetes tipe 2 - Ni Ketut Sutiari; Rimbawan Rimbawan; Clara Meliyanti Kusharto; Purwantyastuti Ascobat; Adi Teruna Effendi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2017)
Background: Status of minerals such as zinc, magnesium, and chromium among diabetic patients are considered lower than non-diabetic peoples, both in the serum and intake. Some reviews show that those minerals contribute to carbohydrate metabolism among diabetic patients.Objective: This study aims to explore intake of zinc, magnesium, and chromium among DMT2 in Denpasar.Method: This is a cross-sectional analytic study. The population was all (70) DMT2 patients registered at Chronic Disease Service (Prolanis) at two Primary Health Care (PHC) Denpasar Utara III PHC and Denpasar Timur I PHC. The sample for the study was DMT2 patients and non-diabetic people age 50-70 years reside in Denpasar city. DMT2 patients were randomly selected with simple random technique, while non-diabetic peoples were non-randomly selected. The level of serum chromium was measured by AAS method, whereas microminerals intake were collected by a recall and SQ-FFQ method. Data was analyzed descriptively and differences were tested with two independent t-test at 95% confidence level.Results: The mean of serum chromium DMT2 and non-diabetic were 0.044 mg/L and 0.094 mg/L respectively. The mean±SEM magnesium (DMT2 316.1±22.4 mg/day; non-diabetic 211.0±33.5 mg/day), zinc intake was (DMT2 8.4±0.7 mg/day; non-diabetic 6.2±0.8 mg/day), and chromium (DMT2 10.8±1.3 µg/day; non-diabetic 8.7±0.9µg/day). A significant difference was found between magnesium intake (p=0.01).Conclusion: The study showed that zinc, magnesium and chromium intake is appeared higher among DMT2 patients compare to non-diabetic in Denpasar region.